Pharmacokinetic features of dolutegravir with rifampicin and rifabutin among patients coinfected with human immunodeficiency virus and tuberculosis/mycobacterium avium complex - Xiaoqin Le; Xiaoye Guo; Jianjun Sun; Li Liu; Yinzhong Shen; Jiangrong Wang; Tangkai Qi; Zhenyan Wang; Yang Tang; Wei Song; Lin Yin; Lijun Zhang; et al. (International Journal of Infectious Diseases, 2022)
Background: Rifamycins are the cornerstone of anti-tuberculosis therapy while they are potent inducers of drug metabolizing enzymes. For the first time, we evaluated the effect of rifampicin (RIF) and rifabutin (RBT) on the pharmacokinetics (PK) of dolutegravir (DTG) in patients with HIV and tuberculosis (TB)/ mycobacterium avium complex (MAC) co-infection. Methods: Both HIV/TB (or MAC) co-infected patients and HIV infected patients without TB/MAC were enrolled. Patients in the RIF group received DTG 50 mg twice daily together with 600mg of RIF, while patients in the RBT group received DTG 50 mg once daily together with 300 mg of RBT. The DTG pharmacokinetic profiles in different groups were assessed. Results: A total of 13 subjects in the RIF group, 12 subjects in the RBT group, and 10 subjects in non-TB/MAC group were enrolled. The geometric mean ratio (GMR) of the trough concentration (Ctr) of DTG in the RIF group to non-TB/MAC group was 1.33 [90% confidence interval (CI):0.97 to 1.81], while the GMR of the maximum concentration (Cmax) of DTG was 1.29 (90% CI: 1.23 to 1.36). The GMR of the Ctr of DTG in the RBT group to non-TB/MAC group was 0.41 (90% CI: 0.30 to 0.57), while the GMR of the Cmax of DTG was 0.55 (90% CI: 0.52 to 0.57). Conclusions: Due to the relatively low trough concentrations of DTG with RBT, DTG 50mg once daily together with RBT could only serve as an alternative option for HIV/TB (or MAC) co-infected patients.